(untitled) (Dhaka University Journal of Biological Sciences, 2023)
While attending university is a conceivably stressful situation, there is growing evidence that a sizable proportion of students suffer from mental health issues. The present study aims to observe the mental health issues, perceived stress, and personality traits among Bangladeshi university students well as to identify whether personality traits are associated with mental health status or perceived stress among university students. 300 conveniently sampled university students participated in a web-based cross-sectional survey that collected demographic information as well as results from the Bangla GHQ-12, Bangla PSS-10, and Bangla BFPT-44 scales. The average score of mental health-related issues and perceived stress was 15.91 and 20.20, respectively. Neuroticism was significantly associated with mental health issues (B = .473, AR2 = .423, 95% CI: .450 to .690) as well as with stress (B = .401, AR2 = .222, 95% CI: .211 to .382). Agreeableness, extraversion, and conscientiousness were also found to be significantly associated with mental health issues and stress (p<.001). Since neuroticism is associated with a higher risk of mental health issues and higher levels of perceived stress in students, and extraversion, conscientiousness, and agreeableness are associated with a lower risk, this information can be used to design preventative and educational programs that focus on these specific personality traits. Dhaka Univ. J. Biol. Sci. 32(2): 233-241, 2023 (July)